Seeded phosphorus retention in fixed-bed laboratory columns by the use of apatites - Delgado-González, Laura; Lartiges, Bruno; Troesch, Stéphane; Proietti, Arnaud; Molle, Pascal (Frontiers in Environmental Science, 2022)
Phosphorus retention in small and medium-sized wastewater treatment plants is crucial to preventing the eutrophication of downstream catchments. One popular solution in combination with treatment wetlands is the use of reactive filters for phosphorus retention; however, identifying a suitable substrate is not an easy task in this process. Apatites have already proven to be an effective alternative for phosphorus retention, yet more in-depth research is needed. This paper uses two natural apatite materials NA1 and NA2 introduced in four fixed-bed laboratory columns to assess their phosphorus retention capacity. Various inflow conditions are set for the NA1 substrate to evaluate the impact of calcium and biomass development on performance. The substrates show high phosphorus retention (>16.8 g PO4-P/kg for NA1 and >17.5 g PO4-P/kg for NA2) as well as high kinetic rate coefficients (1.45 and 1.70 h-1 for NA1 and NA2, respectively), with performances above 80% for both substrates. The maximum phosphorus retention capacity is not attained at the end of the experiments, despite their long duration (230 days) and the short hydraulic residence times applied (~ 2 hours), thus suggesting a long-term removal capacity. The NA1 column fed with a calcium-deficient synthetic solution displays just slightly reduced kinetic rates, most likely due to calcite and dolomite dissolution from the media. The column fed with treated wastewater does not reveal any significant reduction in hydraulic conductivity due to biomass development. No loss of permeability due to chemical clogging is observed in the other columns. Scanning electron microscopy indicates that phosphorus retention occurs by the precipitation of amorphous calcium phosphate for both natural apatites, thereby clearly demonstrating the implementation of seeding mechanisms. Such a retention process is sustainable, which suggests it may proceed over even higher retention capacities.